A solid criterion based on strict LMI without invoking equality constraint for stabilization of continuous singular systems. (November 2017) - Zhang, Xuefeng; Chen, YangQuan
Abstract: The paper considers the stabilization issue of linear continuous singular systems by dealing with strict linear matrix inequalities (LMIs) without invoking equality constraint and proposes a complete and effective solved LMIs formulation. The criterion is necessary and sufficient condition and can be directly solved the feasible solutions with LMI toolbox and is much more tractable and reliable in numerical simulation than existing results, which involve positive semi-definite LMIs with equality constraints. The most important property of the criterion proposed in the paper is that it can overcome the drawbacks of the invalidity caused by the singularity of Ω = PE T + SQ for stabilization of singular systems. Two counterexamples are presented to avoid the disadvantages of the existing condition of stabilization of continuous singular systems. Abstract : Highlights: The stabilization of singular systems is dealt with LMIs without equality constraint. Ω = PE T + SQ .The algorithm overcomes the drawbacks of the invalidity caused by the singularity of O = PE T + SQ. Examples present the practicability of singular circuit systems and show the differences from others. Counterexamples avoid the disadvantages of the existing stabilization of singular systems.